25 years of digital archives of visual materials: what we've done, what we've learned, and what challenges remain. Issue 2 (2nd April 2016) - Besser, Howard
Abstract : In this article, the author looks back at the history of American digital archives of visual materials. Beginning with the Berkeley Image Database in 1986, he outlines the contributions that various projects made to the development of new tools and approaches, focusing on three important projects in which he participated in the decade leading up to 1996. How did both content and metadata change as these projects went from single collections to aggregations of diverse collections? After situating these three projects, the author then briefly covers highlights of other visual collection projects and systems from the subsequent 15 years, discussing their need to evolve from access systems into archival systems. The article concludes with an outlook on past challenges that the field has already overcome and a discussion of the new challenges for digital archives in the future.